2020
DOI: 10.22201/ib.20078706e.2020.91.2912
|View full text |Cite
|
Sign up to set email alerts
|

Producción y calidad de conidios de cepas de entomopatógenos del género Metarhizium anisopliae, aislados en zonas agrícolas del Estado de México

Abstract: ResumenEn la naturaleza, los hongos entomopatógenos pueden eliminar o reducir las plagas agrícolas y constituyen, además el grupo de mayor importancia del control biológico, los géneros sobresalientes en la industria son: Metarhizium, Beauveria, Isaria y Lecanicillium. Los objetivos de este estudio fueron aislar hongos nativos de Metarhizium anisopliae de suelo agrícola del oriente del estado de México, así como evaluar la producción, calidad e infectividad de los conidios obtenidos en comparación a un product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…is lower than that reported by Alcantara-Vargas et al [30], who reported a conidia production of 9 × 10 8 conidia mL −1 of the substrate by M. anisopliae. According to Fargues et al [31] and Alcantara-Vargas et al [30], conidia production by Metarhizium strains can be infuenced by the nutrient content of the culture medium and the production method. Currently, no evaluations of conidia production of other strains of B. peruviensis have been made.…”
Section: Resultscontrasting
confidence: 67%
“…is lower than that reported by Alcantara-Vargas et al [30], who reported a conidia production of 9 × 10 8 conidia mL −1 of the substrate by M. anisopliae. According to Fargues et al [31] and Alcantara-Vargas et al [30], conidia production by Metarhizium strains can be infuenced by the nutrient content of the culture medium and the production method. Currently, no evaluations of conidia production of other strains of B. peruviensis have been made.…”
Section: Resultscontrasting
confidence: 67%
“…Advances in Enzyme Research, 12, 1-15. https://doi.org/10.4236/aer.2024.121001 logical control agents, since they are responsible for causing diseases in insects [1]. Until now, more than 90 genders and 700 species of EF have been described and the isolation of new strains continues, among the most used are: Metarhizum anisopliae with 33.9%, Beauveria bassiana with 33.9%, Cordyceps (=Isaria) fumosorosea with 5.8% and Beauveria brongniartii with 4.1% [2] [3]. EF present a life cycle marked by a stage at which conidia are formed as a form of asexual reproduction, in which fungi remain until adhere to the insect's cuticle [4].…”
Section: Introductionmentioning
confidence: 99%